Carbon Stock and its Management in Soils of Bhilwara District, Rajasthan - and R.S. Singh, R.P. Sharma (Journal of the Indian Society of Soil Science, 2015)
Soil organic matter is an important component that regulates most of the soil properties and serves as an indicator for assessing soil quality and climate change phenomenon. Soil resources of Bhilwara district of Rajasthan were inventorized using the IRS 1B imageries and survey of India toposheet on 1:50,000 scale. The district had three physiographic units viz., Eastern plain, Aravalli and Vindhyan landscape. Out of forty soil series, 22 occurred in Eastern plain, 10 in Vindhyan and 8 in Aravalli landscape. The soils of different physiographic units were evaluated for soil organic carbon (SOC) stock and soil inorganic carbon (SIC) at 0-15, 15-30, 30-50 and 50-100 cm depths. The soils of Aravali landscape, Eastern plain and Vindhyan landscape had SOC pool to the tune of 11.3, 12.1 and 14.8 Mg ha-1 at 0-15cm depth and 6.4, 9.3 and 11.6 Mg ha-1 at 15-30 cm depth, respectively. The SIC pool in these physiographic units were 4.9, 6.1 and 3.1 Mg ha-1 at 0-15cm depth and 3.5, 10.8 and 3.1 Mg ha-1 at 15-30 cm depth, respectively. Among soil orders, Vertisols (3.69% of total geographical area, TGA) sequestered highest SOC (77.1 Mg ha-1) and SIC (148.5 Mg ha-1) up to profile depth followed by Inceptisols (68.85% of TGA) and Entisols (10.32% of TGA).